Historical guide to world media freedom : a country-by-country analysis - Whitten-Woodring, Jenifer; Van Belle, Douglas A., 1965- (Los Angeles : SAGE Reference/CQ Press, 2014)
Scholars of international relations and international communications view the extent of media freedom from country to country as a key comparative indicator either by itself or in correlation with other indices of national political and economic development. This book provides consistent and comparable measures of media freedom in all independent countries for the years 1948 to the present.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Freedom of the press; Government and the press; Mass media -- Censorship; Censorship; Freedom of expression